The combined use of various forms of micronized progesterone in the treatment of the threat of termination of pregnancy in multiple pregnancies - І. М. Нікітіна (Publishing House TRILIST, 2017)
The article highlights the data on the features of the etiology and pathogenesis of the threat of premature birth in a multiple pregnancy. The results of a clinical study of the effectiveness of combined therapy in the threat of termination of pregnancy in women with multiple pregnancies with sublingual and vaginal forms of micronized progesterone are presented. In the course of the study 120 twins pregnancies with signs of miscarriage in terms of 14-28 weeks were analyzed. The first group consisted of 40 women who were offered a sublingual form of natural micronized progesterone in combination with the vaginal form (drug Luteina) in the scheme of treatment and prophylactic measures. The second group included 40 women, who received a synthetic progesterone preparation (dydrogesterone) for treatment of the threat of termination of pregnancy. The control group consisted of 40 pregnant women, who were treated according to the current clinical protocols. The results of the study showed that the effect of the use of the sublingual form of micronized progesterone in the period of severe clinical symptoms of the threat of premature delivery in multiple pregnancy came out twice as fast compared to the oral form of synthetic dydrogesterone, what contributes the rapid elimination of clinical symptoms, regression of ultrasound markers of the threat of miscarriages and prevents further progression of cervix structural changes. The presence of sublingual and vaginal form of micronized progesterone allows, if necessary, to go from one form to another, and also combine both forms to quickly saturate the body of pregnant woman by progesterone in conditions of gestagen deficiency in order to eliminate the symptoms of the threat of pregnancy termination. Therefore, complex therapy of the threat of premature birth with the use of sublingual and vaginal forms of micronized progesterone has a significant therapeutic effect, contributes to a shorter period of inpatient stay, a reduction in the number of complications compared to other progestins and can be recommended for widespread use. The use of natural micronized progesterone in women with the threat of interruption of pregnancy in multiple pregnancies significantly reduces the risk of preterm labor and improves perinatal outcomes.